Understanding live coding events. Issue 2 (2nd July 2016) - Burland, Karen; McLean, Alex
ABSTRACT: As an arts practice, live coding has strong roots in musical performance, and the fact that its 'liveness' requires the performer to write and modify algorithms in real time [Collins, N., A. McLean, J. Rohrhuber, and A. Ward. 2003. "Live Coding in Laptop Performance." Organised Sound 8 (3): 321–330] means that it is often treated as a kind of music improvisation. Organised live coding has now passed its tenth year [Magnusson, T. 2014. "Herding Cats: Observing Live Coding in the Wild." Computer Music Journal 38 (1): 8–16], and during this decade it has been manifested in a variety of contexts. Whilst there is a growing body of research addressing aspects of live coding from the coder's perspective, little is known about the audiences for these events. Using an online questionnaire, this paper seeks to explore the motivations, experiences, and responses of live coding audiences and to examine their perceptions of the projected source code during live coding events. We aim to shed new light on the role of openness and technology in live coding performances, providing rich context for fuller understanding of this emerging practice and its impact on audience experience.